(untitled) (Journal on Excellence in College Teaching, 2024)
This study examined how one set of instructors’ stated classroom teaching philosophies did or did not manifest during their first day of class. Data included classroom observations, interviews, and content analysis of syllabi. Findings suggest that instructors employed learner-attentive rather than learner-centered practices on the first day, a potentially important nuance when assessing teaching practices. The author encourages instructors to consider more deeply the pedagogy that undergirds their every act in the classroom and what certain enactments might communicate to their students, from the practice to developing, distributing, and reviewing syllabi to the contexts in which first-day activities take place.